Defying out-group impoliteness: an analysis of users’ defensive strategies in disputing online criticisms - Isma Noornisa Ismail,; Thilagavathi Shanmuganathan,; Azianura Hani Shaari, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Online social networking sites have become an integral platform in the development of relationships among Internet users around the world. The Internet has made connectivity faster and stronger than the old days. However, studies have shown that many have misused this platform to incite hatred and animosity when expressing themselves. Online derogatory expressions include the usage of slurs, pejoratives, hate-speech, flaming, and trolling, among others. The present study aims to analyse defensive strategies employed by Facebook commenters on the issue of 1MDB. Three threads of comments and responses towards the political scandal of 1MDB were identified and extracted from Facebook newspaper page. The data was then analysed using the summary of response options and the list of defensive counterstrategies offered by Bousfield (2007). The findings demonstrated the use of defensive strategies by the participants in disputing criticisms of 1MDB issues, particularly comments affecting the reputation of their social group and ethnicity. Most of the participants chose to contradict the opposition directly; and some of them included statements of clarification, explanation or details about the issue together with the arguments. The discussion of the findings offers some novel insights into the field of impoliteness by drawing attention to online users’ defensive linguistic behaviour in dealing with out-group impoliteness strategies in online communication.